Diversity of insect in the paddy field at Kampung Pengkalan Samak, Merlimau, Melaka / Aizam Ashrawi Arzemi - Arzemi, Aizam Ashrawi (Faculty of Plantation and Agrotechnology, 2019)
The studying insect diversity that was conducted in a paddy field at Kampung Pengkalan Samak which is located at Merlimau, Melaka. There have a set at two different locations with a six replication each of location that had made during the six-week observation. The data were collected in three time for a one-week observation to reduce from the body insect decaying. A sampling method were use a yellow pan trap which is use a colourless detergent as a trapping method and yellow colour of the pan be an attractive to insect. A number of individual has been collected were 4806 with 81 species that has been identified in 11 Order that has been recorded includes the Coleoptera, Hymenoptera, Diptera, Orthoptera, Hemiptera, Odonata, Blattodea, Lepidoptera, Neuroptera, Thysanoptera and also a Aranea. An insect that has been collected were classed by their species and Order that a different between the location of the sampling observation were some of them has different and some are no different. There has a dominant insect that has classified by Order in the field ecosystem were Hemiptera followed by the lowest order was Thysanoptera. A result by the observation that has been made, there has a balance ecosystem with the pest and non pest insect in term of their distribution on both of location trap. There some order distribution on the side field and also some distribution on the middle field. However, there still has a balance distribution for a certain Order which is has in a both location. This is show on how the biological control can reduce the pest population in the rice field ecosystem and sustainable food security.